POTENTIAL OPTIMIZATION OF TOBACCO AGRICULTURE WASTE IN WATUBONANG VILLAGE, BADEGAN DISTRICT, PONOROGO - Rochmah Kurnijasanti; Sri Agus Sudjarwo; Kadek Rachmawati (Universitas Airlangga, 2023)
The aims of this community dedication: 1) Improve the economy of the villagers of Watubonang and Biting, Badegan Ponorogo district through changing mindsets to improve people’s welfare 2) Increasing the knowledge and skills of the villagers of Watubonang and Biting, Badegan Ponorogo district through technology transfer for making pecticide formulations, antiscabies drugs, antiseptik, compost manure disinfectant, dipping solution based on tobacco waste. The result of the communiy dedication implementation showed an increase in participants on how to manufacture various kinds of tobacco waste products from 6.7% to 93.3% and an increase in the skills of participants on how to manufacture various kinds of tobacco waste products from 6.7% to 93.3%. in addition to the increased knwoledge and skills of the community dedication participants in Watubonang and Biting villages, Badegan Ponorogo district, it showed a decrease in the average cost of using medicines, antiseptiks, and disinfectants per house from 210 thousand rupiah to 42 thousand rupiah. Form the results of community dedication in the villages of Biting and Watubonang, Badegan Ponorogo district, it is hoped that they will become fostered villages of FKH Unair.